KEBIJAKAN PENDIDIKAN DI TINJAU DARI SEGI HUKUM KEBIJAKAN PUBLIK - Tri Puji Hastuti; Soehartono Soehartono (Muhammadiyah University Press, 2018)
Nation education system is a system which integraded from all unit and education activities which related each other to reach national education purpose. Because of Indonesia education renewal demand, education wisdom has been through many changes. In this matter, education wisdom is viewed from public wisdom which is made by country, executive, legislative, judicative.Making decision about national education system is related with public wisdom. Public wisdom is new science because historically it appears in the midlle 1960 as a discipline in public administration and politic.The important matter which become attention is education wisdom that park from public wisdom. Research which is done by researcher is diagnostic research. This research uses doctrinal (normative) method and has purposeto know the base of public wisdom in education and analyze public wisdom in education